Hydration-induced phase separation in amorphous solid dispersions - Dovrén, Simon (My University, 2025)
Amorphous solid dispersions (ASDs) are pharmaceutical formulation in which a drug is molecularly dispersed within a carrier matrix. ASDs are designed to address the challenges of drugs with low solubility in their crystalline state. The carrier matrix, typically a polymer, stabilises the drug in its amorphous phase, which enhance solubility and dissolution rates of the drug. This thesis examines ASDs composed of the drug indomethacin and the polymer PVPVA as carrier, with the objective to correlate hydration-induced phase sepa ration to drug release behaviour, and test the stability of ASDs in a humid en vironment. Samples of varying drug concentrations, both pristine and hydrated, were analysed using small-angle X-ray scattering (SAXS), to understand the phase separation processes on the nanoscale. The molecular mobility in the samples was analysed with differential scanning calorimetry (DSC) and the drug release was measured through dissolution tests. Nanoscale phase separation was found to occur upon exposure to a neutral buffer, for drug loadings >10%, after absorbing >40% buffer. Higher drug load and buffer concentration led to a higher degree of phase separation and the formation and stabilisation of drug-rich domains with distinct interfaces. The phase separation impacted the dissolution properties, as samples with 5% and 10% drug load had faster drug release, in comparison to the samples with 20% and 30% drug load. Phase separation was also found in samples with 30% drug load after being exposed to 98% relative humidity for 10 weeks. The sample did not crystallise, indicat ing a stable system. These results offer insight into the phase behaviour of ASDs upon dissolution and exposure to humidity, though additional investigation of ASDs in acidic conditions would enhance the understanding of in vivo phase separation processes.
Keywords: Amorphous Solid Dispersion (ASD), small-angle X-ray scattering (SAXS), wide-angel X-ray scattering (WAXS), phase separation, homogenuous, heteroge neous, polydispersity